2018
DOI: 10.1093/gerona/glx250
|View full text |Cite
|
Sign up to set email alerts
|

Death, Depression, Disability, and Dementia Associated With Self-reported Hearing Problems: A 25-Year Study

Abstract: Our study confirms the strong link between hearing status and the risk of disability, dementia, and depression. These results highlight the importance of assessing the consequences of treating hearing loss in elders in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(110 citation statements)
references
References 36 publications
3
103
0
4
Order By: Relevance
“…The recent conclusions by Inserm Bordeaux (January 2018) on the follow-up of the Paquid cohort merit reiterating here: 3777 participants over the age of 65, over 25 years. They confirm the direct link between the hearing profile of the patients included and the risk of invalidity, dementia and depression (17). Another recent publication of the Journal of European Psychiatric Association concluded that Tomatis training significantly improved subjects' cognitive functioning.…”
Section: C) Clinical Improvementsupporting
confidence: 58%
See 1 more Smart Citation
“…The recent conclusions by Inserm Bordeaux (January 2018) on the follow-up of the Paquid cohort merit reiterating here: 3777 participants over the age of 65, over 25 years. They confirm the direct link between the hearing profile of the patients included and the risk of invalidity, dementia and depression (17). Another recent publication of the Journal of European Psychiatric Association concluded that Tomatis training significantly improved subjects' cognitive functioning.…”
Section: C) Clinical Improvementsupporting
confidence: 58%
“…Does a subject's initial average level of hearing play a role in the responsiveness or resistance to sound stimulation? Does a change in hearing level constitute a risk factor in mental health (17)(18)(19) ?…”
Section: A) Listening Testmentioning
confidence: 99%
“…Interestingly, in a subsequent study conducted within the same population-based cohort (i.e., PAQUID study), these results were replicated on the risk of developing dementia [30]. Adjusting for age, gender and educational level, an increased risk of developing dementia was found for participants reporting hearing loss compared to participants reporting normal hearing.…”
Section: Potential Benefits Of Hearing Aids On Cognitionmentioning
confidence: 81%
“…Although still limited in number, these studies report consistent results, supporting the hypothesis of an increased risk of dementia which remains significant even after statistically accounting for potential confounders such as demographic and/or cardiovascular factors. Such results have been gathered from studies considering hearing loss either with audiometric measures [15,27,28], speech recognition tests [29], or indirect/self-reported measures [30][31][32]. Although most of the studies considered peripheral hearing loss, the link between age-related central auditory processing disorder [33] and cognitive decline and/or dementia has also been reported by two longitudinal studies [34,35].…”
Section: Hearing Loss and Age-related Cognitive Decline: Two Highly Fmentioning
confidence: 99%
“…Studying the association between hearing impairment and depression may therefore have major clinical and public health implications, especially when considering that hearing impairment is a modifiable condition in most cases. The few existing prospective studies on hearing impairment and depression mostly used self-reported status of hearing impairment (15)(16)(17), were of relatively small size (n<900) (16,17), and have so far provided mixed results (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%